Left atrial remodeling and voltage-guided ablation outcome in obese patients with persistent atrial fibrillation - Marzak, Halim; Fitouchi, Simon; Labani, Aïssam; Hammann, Justine; Ringele, Romain; Kanso, Mohamad; Cardi, Thomas; Schatz, Alexandre; Ohlmann, Patrick; Morel, Olivier; Jesel, Laurence (Frontiers in Cardiovascular Medicine, 2024)
Background: Obesity is a risk factor of atrial fibrillation (AF). Data regarding left atrial (LA) remodeling in obese are scarce. Whether obesity favors AF recurrence after catheter ablation (CA) is still controversial. We assessed the distribution of epicardial atrial fat on computed tomography (CT) scan, LA bipolar voltage, low-voltage zone (LVZ) extent and the outcome of voltage-guided ablation of persistent AF in obese and non-obese.Methods: 139 persistent AF patients undergoing a first voltage-guided ablation were enrolled and divided into two groups: 74 non-obese and 65 obese. Epicardial adipose tissue (EAT) was assessed on a CT scanner. LA endocardial voltage maps were obtained using 3D mapping system in sinus rhythm. LVZ was defined as < 0.5 mV.Results: LA volume, voltage and EAT amount were similar in two groups. LVZ were less frequent in obese (12 [18.8%] vs 26 [35.1%], p= 0.05), particularly on anterior wall. The posterior and lateral EAT were correlated respectively with posterior and lateral LVZ extent in obese. After 36 months follow-up, AF-free survival rate was similar. Lateral EAT (OR 1.21, 95% CI, 1-1.4, p=0.04) and P-wave duration (OR 1.03, 95% CI, 1-1.05, p=0.03) but not BMI were predictors of AF recurrence after CA.In obese, LVZ was less marked than in non-obese with similar LA volumes, voltage and EAT amount. In obese, posterior and lateral EAT were correlated with posterior and lateral LVZ extent. Obese had a similar and favorable 36 months outcome after AF ablation. BMI was not predictive of AF recurrence.